An intronic SNP affects skeletal muscle development by regulating the expression of TP63 - Chen, Yufen; Wang, Zhen; Qu, Xiaolu; Song, Bangmin; Tang, Yueting; Li, Bugao; Cao, Guoqing; Yi, Guoqiang (Frontiers in Veterinary Science, 2024)
Understanding the mechanisms underlying porcine skeletal muscle development is essential for the genetic improvement of meat production traits. TP63, a transcription factor, plays a pivotal role in regulating fundamental cellular processes such as cell cycle progression, apoptosis, and genome stability. However, the role and the underlying mechanisms of TP63 in skeletal muscle cell proliferation remain poorly understood. In this study, we investigated the effects of TP63 on skeletal muscle cell viability and proliferation using mouse and porcine skeletal muscle myoblasts.Selective sweep analysis revealed significant selection on TP63 in Western pigs, indicating its potential as a candidate gene driving skeletal muscle development. Quantitative real-time PCR (RT-qPCR) demonstrated a positive correlation between TP63 overexpression and skeletal muscle cell proliferation. Furthermore, bioinformatics analysis predicted an interaction between MEF2A, a transcription factor, and the mutation site of TP63. This prediction was validated by dual-luciferase assay, revealing that the candidate enhancer SNP could affect the binding of MEF2A and then regulate TP63 expression, which collaboratively promoted skeletal muscle cell proliferation. These findings provide experimental evidence for further investigating the mechanisms of skeletal muscle development and accelerating genetic breeding strategies.